2008
DOI: 10.2106/jbjs.g.00679
|View full text |Cite
|
Sign up to set email alerts
|

Primary Arthroscopic Stabilization for a First-Time Anterior Dislocation of the Shoulder

Abstract: Following a first-time anterior dislocation of the shoulder, there is a marked treatment benefit from primary arthroscopic repair of a Bankart lesion, which is distinct from the so-called background therapeutic effect of the arthroscopic examination and lavage of the joint. However, primary repair does not appear to confer a functional benefit to patients with a stable shoulder at two years after the dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 35 publications
2
149
1
2
Order By: Relevance
“…These five recurrent instabilities indicate a total instability of 19 %, which is comparable with previously described recurrence rates from other studies investigating immobilization in external rotation of shorter follow-up periods and in similar patients of average age [3,4,7] (see also Table 2). As well as in the immobilization of internal rotation [22] or in the operative treatment groups [24], our data show that in external rotation the majority of re-dislocations occur within the first 2 years after initial trauma (3-24 months, ø 12.2 months). The specific reasons for the re-dislocation or instability remain difficult to determine.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These five recurrent instabilities indicate a total instability of 19 %, which is comparable with previously described recurrence rates from other studies investigating immobilization in external rotation of shorter follow-up periods and in similar patients of average age [3,4,7] (see also Table 2). As well as in the immobilization of internal rotation [22] or in the operative treatment groups [24], our data show that in external rotation the majority of re-dislocations occur within the first 2 years after initial trauma (3-24 months, ø 12.2 months). The specific reasons for the re-dislocation or instability remain difficult to determine.…”
Section: Discussionmentioning
confidence: 71%
“…The most recently published studies by Finestone et al [6] and Liavaag et al [7] deemed the operative treatment to be the more efficient treatment for primary traumatic dislocation, even though a direct comparison between immobilization in external rotation and surgery is not available as a randomized controlled trial. In contrast to immobilization in internal rotation, recurrence rates of operative treatment are clearly superior [24,[26][27][28]. Although the risks for surgery, especially in arthroscopic stabilization, are low [28][29][30], these risks have to be considered and disclosed to the patient during the decision-making process.…”
Section: Studymentioning
confidence: 99%
“…[30] Bankart lesion repair by arthroscopy [34] Case Procedure: Return of dislocation [1] Control Procedure: Return of dislocation [2] Limitation of external rotation [1] Robinson et al 2008 Bankart lesion repair by arthroscopy [39] Case Procedure: Recurring dislocation [3] Pain and stiffness [4] Need for surgical repair [1] Control Procedure: Recurring anterior dislocation [24] Subjective instability [1] Pain and stiffness [4] Bottoni et al 2002…”
Section: Resultsmentioning
confidence: 99%
“…A study by Wintzell et al, which aimed to evaluate the effect of arthroscopic lavage as a form of treatment for acute anterior glenohumeral dislocation, reported a recurrence rate of 43% in patients who received nonsurgical treatment, while that of patients who received arthroscopic lavage was only 13%. (26) Robinson et al (27) found that arthroscopic repair of a Bankart lesion after primary traumatic anterior shoulder dislocation reduced the risk of recurrence by 76%; they also found that the risk of all recurrent instability was reduced by 82% in this group of patients that underwent Bankart repair, as compared to the group that underwent arthroscopy and lavage alone. They concluded that marked treatment benefit could be derived from primary arthroscopic repair of a Bankart lesion, distinct from the so-called background therapeutic effect of arthroscopic examination and lavage of the joint.…”
Section: Surgical Treatmentmentioning
confidence: 92%
“…However, they noted that primary repair did not appear to confer a functional benefit to patients with a stable shoulder at two years after the dislocation. (27) In a study that evaluated the results of early arthroscopic Bankart repair in patients with primary traumatic anterior dislocation of the shoulder, Valentin et al (28) found that 93% of their patients had good or excellent results at 18 months. In addition, 83% of their patients returned to their pre-dislocation activity level.…”
Section: Surgical Treatmentmentioning
confidence: 99%